Does Transparency Promote Engagement? Cancer Patients' Access of Electronic Medical Records Before and After the Information Blocking Rule - Polubriaginof, Fernanda C G; Chimonas, Susan; Lipitz-Snyderman, Allison; Spiegelhoff, Zoe; Seier, Kenneth; White, Charlie; Jorvina, Joshua; Kuperman, Gilad (AMIA ... Annual Symposium proceedings, 2024)
Access to clinical information is critical to support patient engagement. The 21 Century Cures Act grants patients immediate electronic access to their full medical records. To assess the potential impact of this transparency provision, we conducted a retrospective study in a large cancer center in New York City, focusing on clinically active patients' accessing health information shared via the patient portal. We identified a significant increase (14%) in the number of pathology and radiology reports read by patients after the implementation ofimmediate release of reports. No changes were found in the rates of account creation or logins. Our results suggest that oncology patients show strong, consistent interest in their clinical data, with many taking advantage of the full electronic access granted by Cures. These findings shed new light on this legislation's impact on patient engagement and access to clinical data.